The Oxford handbook of hedge funds - Cumming, Douglas; Johan, Sofia A.; Wood, G. (Geoffrey) (Oxford : Oxford University Press, 2021)
A comprehensive overview of the hedge fund industry from a global perspective, bringing together insights from theoretical and applied research. The book seeks to both introduce the industry and what it does to scholars and practitioners new to the area, and to provide more advanced insights to those with extensive expertise in the area. The handbook explains the main context in which hedge funds operate, how the raise capital, and their structure and governance. It evaluates the main factors that have affected the operation of hedge funds, including competition from mutual funds, the market environment, and financial regulation, explains key concepts such as hedge fund flows, and core issues of practice, such as hedge fund manager fees.
Introducing Hedge Funds / Douglas Cumming, Sofia Johan, Geoffrey Wood -- Optimal Embedded Leverage for Porfolios of Commodity Trading Advisors / Christian Lundström Tjurhufvud, Jarkko Peltomäki -- Convergence and Diversity in the Hedge Fund and Private Equity Industry / Omololu Bajulaiye, Mark Fenwick, Ivona Skultetyova, Erik P. M. Vermeulen -- Financial Technology and Hedge Funds / Wulf A. Kaal -- Hedge Funds and Herding Behaviour / Neil M. Kellard -- Hedge Fund Activism and Financial Performance / J. B. Heaton -- Hedge Fund Activism and Corporate Innovation / Roberto S. Santos, Sunny Li Sun -- Locating Hedge Funds in a Subjective Political Economy Context / Ian Clark, Emrah Karakilic -- Misconduct at Hedge Funds / Nicolas P. B. Bollen -- Hedge Funds and Financial Misreporting / Philippe Jorion -- Outsourcing Compliance Functions and Fraud Detection / David M. Shapiro -- Indirect Regulation of Hedge Funds / Wulf A. Kaal -- Hedge Funds Strategies in the Post-Crisis Era / Yigit Atilgan, Turan G. Bali, A. Doruk Gunaydin -- Hedge Fund Flows / Guillermo Baquero, Marno Verbeek -- A Review of Hedge Fund Activism: Impact on Shareholders vs. Stakeholders / Hadiye Aslan -- Gone Global: The International Diffusion of Hedge Fund Activism / Ruth V. Aguilera, Ryan Federo, Yuliya Ponomareva -- Hedge Funds and Limited Partnership Agreements / Na Dai -- Tax Optimization of Hedge Funds / Francois-Serge Lhabitant -- The Lost Decade for Hedge Funds: Three Threats / Joseph A. McCahery, F. Alexander de Roode -- Hedge Fund Activism vs Other Activist Investors / Ulf von Lilienfeld-Toal, Jan Schnitzler -- Investment Strategies of Hedge Funds / Hany A. Shawky.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 10, 2021).
Keywords: Hedge funds